Vocational Class Organizer for Inclusive Students at Mutiara Bunda Elementary School (Current Research in Education: Conference Series Journal, 2024)
In holding this vocational class to gain experience in managing various differences in one class. develop each student to have their own uniqueness, a sense of empathy and sensitivity to student limitations. This research method uses qualitative methods with literature studies which we carry out by means of observation, interviews and documentation. To train fine and gross motoric skills in inclusive students, in order to train students' skills and independence for everyday life and life in the future. Vocational classes in inclusive education are an important component in efforts to create an inclusive educational environment and focus on developing practical skills that are relevant for all students, including students with special needs. Implementing vocational classes in inclusive schools involves a series of designed steps and practices such as curriculum preparation, evaluation/identification of student needs, as well as program and material adjustments. Providing vocational classes in accordance with the stated objectives, namely developing the potential of each student, specifically for students with special needs. The provision of vocational classes also has a number of significant implications, especially for school residents, such as developing daily living skills and increasing practical skills.